2014
DOI: 10.1089/hum.2014.003
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of Human Glial Cell Line-Derived Neurotrophic Factor from Integration-Deficient Lentiviral Vectors is Neuroprotective in a Rodent Model of Parkinson's Disease

Abstract: Standard integration-proficient lentiviral vectors (IPLVs) are effective at much lower doses than other vector systems and have shown promise for gene therapy of Parkinson's disease (PD). Their main drawback is the risk of insertional mutagenesis. The novel biosafety-enhanced integration-deficient lentiviral vectors (IDLVs) may offer a significant enhancement in biosafety, but have not been previously tested in a model of a major disease. We have assessed biosafety and transduction efficiency of IDLVs in a rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Examination of reporter gene (enhanced green fl uorescent protein, eGFP ) and therapeutic transgene (glial cellderived neurotrophic factor, GDNF ) expression has shown efficient, long-lived, and transcriptionally targeted expression from IDLVs in the striatum of injected rats. We have confi rmed the lack of signifi cant integration of IDLVs in injected rat brains by linear amplifi cation-mediated PCR analysis followed by deep sequencing and insertion site analysis [ 17 ].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Examination of reporter gene (enhanced green fl uorescent protein, eGFP ) and therapeutic transgene (glial cellderived neurotrophic factor, GDNF ) expression has shown efficient, long-lived, and transcriptionally targeted expression from IDLVs in the striatum of injected rats. We have confi rmed the lack of signifi cant integration of IDLVs in injected rat brains by linear amplifi cation-mediated PCR analysis followed by deep sequencing and insertion site analysis [ 17 ].…”
Section: Introductionmentioning
confidence: 76%
“…Very recently, we have assessed biosafety and transduction efficiency of IDLVs in an animal model of Parkinson's disease, the 6-hydroxydopamine (6-OHDA)-lesioned rat , with IPLVs used as a reference [ 17 ]. Examination of reporter gene (enhanced green fl uorescent protein, eGFP ) and therapeutic transgene (glial cellderived neurotrophic factor, GDNF ) expression has shown efficient, long-lived, and transcriptionally targeted expression from IDLVs in the striatum of injected rats.…”
Section: Introductionmentioning
confidence: 99%
“…Local release of NT-3 also reduces astrogliosis, a main cause of MS plaque formation4041. GDNF, a member of the TGF-β superfamily42, promotes survival and differentiation of dopaminergic and motor neurons4344, selectively enhances regrowth of damaged axons45, and induces myelin formation1846. BDNF is well-known to promote neuronal survival and axonal growth4748.…”
Section: Discussionmentioning
confidence: 99%
“…Research later reported that prior peripheral LV immunization elicited an immune response to a subsequent CNS-injected LV only when both LVs encoded the same transgene (Abordo-Adesida et al, 2005). Since LVs are integration proficient, there’s a risk of insertional mutagenesis, and therefore integration-deficient vectors have been used as well (Lu-Nguyen et al, 2014). Recently, a first-ever LV-based Phase I PD clinical trial was completed (Table 5).…”
Section: Delivery Systemsmentioning
confidence: 99%